Um estudo sobre ambiente IoT e seus aspectos de segurança - SILVA, Raíssa Lorena Silva da (2020)
The Internet of Things (IoT) is a new technological concept that allows the adaptation of everyday devices to transmit information to the Internet. That is, it is an Internet architecture capable of connecting several intelligent devices, providing the integration of both physical and digital world. IoT devices are able to perform tasks and use the Internet for sending or consuming information that may or may not need human intervention. The Internet is a hostile environment during the traffic of information; data can be captured and / or altered compromising information and privacy of users. In this context, this work aims to present a study on the security in IoT environments, aiming mainly at the secrecy of information.